Digital preservation of journals at UNAM and institutional repositories: an approach - Villanueva Rivas, Daniel (2015)
The purpose of this document is to provide the experience of migration and digital preservation of technical and scientific journals acquired by purchase by the UNAM. It deals in general with the characteristics of the printed collections of the UNAM, with updated data on these collections, and presents the state of the art regarding print subscriptions through some of the hard data updated to 2014. This paper also delivers a sketch of some digital preservation projects at UNAM (repositories), with the view of UNESCO regarding them, and introduces the three major collaborative digital preservation projects and their characteristics, advantages and disadvantages, organized by librarians and publishers jointly named Portico, LOCKSS and CLOKSS. The libraries that make up the Library System of the UNAM have a common denominator regarding print subscriptions called missing. This shortfall is due to several factors that have to do specifically with the logistics of sending, receiving and controlling subscriptions, which makes users suffer and therefore the staff working in the libraries. The challenge of the model of acquisition in electronic format has to do with ensuring continuous and permanent access called perpetuity, and provide consultation and access despite future technological changes. Hence, despite signed contracts with publishers’ perpetual access and the benefits regarding the accessibility and availability of collections, UNAM raised the need for a secure access of different external editors that can work in case of failure or suspension of service, called digital preservation of collections.